IDENTIFIKASI DAN STRATEGI PERAWATAN ULKUS DIABETIK BERBASIS SISTEM PAKAR - Cahyanto, Heri Nur (Jurnal Biosains Pascasarjana, 2015)
AbstractÂ The occurrence of cases of amputation due to diabetic ulcers are caused by a lack of knowledge of high society, especially patients with diabetes mellitus on the ulcer treatment. This is due to lack of awareness of personal health check and some nurses are not experts in identifying diabetic ulcers. The identification process is not done properly resulting in an error treatment. Every medical personnel have the ability to identify different diabetic ulcers, treatment strategies and appropriate health education can prevent an increase in the degree of ulcers, amputation and the incidence of recurrent ulcer. Therefore, in this study, carried out to identify the application design with a diabetic ulcer-based expert system. The application design is done in several stages. Steps being taken is the collection of data for the knowledge base, mapping logic paths, manufacture Graphic User Interface (GUI), the making inference engine, weighting and system testing to determine the level of accuracy of the system. This study resulted in the identification of applications for intelligent systems based Diabetic Ulcers with the best accuracy rate amounted 81.25%, with the number of nodes traversed is 30 to 100 nodes.Â Keywords: Treatment Diabetic ulcers, ulcers Identification, Expert System.